Bridging Cognition and Pedagogy: A Transcendental Meditation-Based Deep Learning Model in English Language Teaching - Ni Wayan Surya Mahayanti; Ni Wayan Monik Rismadewi; Nice Maylani Asril; Luh Ayu Tirtayani (English Education Department STKIP Agama Hindu Singaraja, 2026)
Recent advances in English Language Teaching (ELT) emphasize deep learning approaches that promote higher-order thinking skills; however, insufficient attention has been given to students’ cognitive readiness as a prerequisite for meaningful engagement. While Transcendental Meditation (TM) has been widely reported to enhance psychological wellbeing and attention, existing studies largely focus on general outcomes rather than its integration within subject-specific pedagogy and its effect on higher-order literacy processes. Addressing this gap, the present study aims to (1) design a TM-based deep learning instructional model for ELT and (2) examine students’ perceptions of its integration in learning. This study employed a design-based research approach combined with qualitative inquiry, involving Grade 10 students. Data were collected through a student perception questionnaire, reflective journals, and focus group discussions (FGDs). The intervention model was implemented through a structured five-phase learning cycle: cognitive centering (TM), activation of prior knowledge, deep engagement, collaborative knowledge construction, and reflective metacognition. Data were analyzed using descriptive statistics and thematic analysis. The findings reveal that the TM-based model effectively supports students’ concentration, emotional stability, and readiness to learn, which subsequently enhances their engagement in complex literacy tasks. Students perceive TM as an integral component of learning that facilitates clearer thinking, reduced anxiety, and deeper comprehension. The study contributes a novel pedagogical framework that integrates cognitive preparation with deep learning processes in ELT. Pedagogically, the findings suggest that embedding TM within instructional design can optimize students’ cognitive conditions, enabling more effective engagement with higher-order language tasks. This highlights the importance of incorporating cognitive-affective readiness into contemporary ELT practices for future research, including investigating long-term impacts and broader classroom applications.